2022
DOI: 10.18502/ijph.v51i11.11167
|View full text |Cite
|
Sign up to set email alerts
|

Side Effects after mRNA COVID-19 Vaccine as a Booster in Health Workers

Abstract: Background: In Indonesia, around 400 health workers died due to Covid-19 between June-July 2021, therefore the health workers need to be given further immunity. Health workers were among the first to get a booster shoot. However, they may experience side effects after vaccination. We aimed to describe side effects of Moderna vaccine as a booster in health workers. Methods: A cross sectional study was conducted on health workers who received mRNA Covid-19 vaccine booster (Moderna) at Sulianti Saroso Infec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 13 publications
1
4
0
2
Order By: Relevance
“…It might be because the number of female respondents is higher than males (74.8% vs 25.2%). This study result is similar with the previous study by Pakki et al among health workers that 45.6% subjects were <35 years, which also indicated gender has no relationship with AEFI [12]. A study by Hidayat et al found that there was a significant relationship between the appearance of AEFI symptoms and a previous history of allergies [19].…”
Section: Aefis With Systemic Symptomssupporting
confidence: 90%
See 2 more Smart Citations
“…It might be because the number of female respondents is higher than males (74.8% vs 25.2%). This study result is similar with the previous study by Pakki et al among health workers that 45.6% subjects were <35 years, which also indicated gender has no relationship with AEFI [12]. A study by Hidayat et al found that there was a significant relationship between the appearance of AEFI symptoms and a previous history of allergies [19].…”
Section: Aefis With Systemic Symptomssupporting
confidence: 90%
“…Meanwhile another study in USA showed 89.35% were females and the remaining were males among mRNA-1273 vaccine recipients, with 6.02% belong to the age group between 18-30 years and the mean of the age was 43.76 years [20]. Other study in Indonesia among healthworkers, conducted by Pakki et al showed different results such as female were 67.3%, and male were 33.7%, while 28.7% had history of COVID-19 and 10.9 had comorbidities [12].…”
Section: Characteristics Of Subjectmentioning
confidence: 95%
See 1 more Smart Citation
“…We found that almost all participants (96%) developed at least one adverse effect after the first booster dose. Literature supports this finding since two other studies found that all participants had adverse effects after the first booster dose [20,21]. Other studies found also high prevalence of adverse effect after the first booster dose ranging from 74.7% to 89% [1417,22,23].…”
Section: Discussionmentioning
confidence: 67%
“…Affordable and wholesome foods are the preference of most people, while consumption of meat and processed foods has declined. The habits and dietary structure of people have been gradually modified as the demand for eliminating sub-health and preventing the occurrence of diseases has increased [2] . The industries that focus on slowing down aging, improving immunity, and maintaining the health of life, are expected to continue to exhibit a significant rise.…”
Section: Introductionmentioning
confidence: 99%